New and long-awaited recruitment of the Critically Endangered species Pinna nobilis in the Mar Menor lagoon (SE Spain, Murcia) - MARTÍNEZ-MARTÍNEZ, PILAR; GIMÉNEZ-CASALDUERO, FRANCISCA; FERNÁNDEZ-TORQUEMADA, YOLANDA; MURCIA, JAVIER; MONTANO-SIMÓN, ALICIA; CORTÉS-MELENDRERAS, EMILIO (Mediterranean Marine Science, 2025)
The bivalve mollusk Pinna nobilis is critically endangered. The specimens from the Mar Menor coastal lagoon constitute one of only two surviving populations in Spain. Due to the eutrophic conditions and environmental collapse of the lagoon, the number of living individuals has been drastically reduced. Furthermore, these conditions, along with other factors, have made it difficult for the species to reproduce successfully. In this report, a new recruitment of individuals detected in the Mar Menor is described for the first time in years. It was considered their spatial and size distribution, and their estimated age.